Pengaruh Retakan Terhadap Nilai Kohesi Dan Sudut Geser Internal Pada Peristiwa Kelongsoran Lereng: The Effect Of Crack Propagation Againsts Cohesion Value And Internal Frictiction Angle Towards Avalanche On The Slope - Rizkan Maulidi Ansyari (Media Ilmiah Teknik Sipil, 2023)
Avalanche often happened during a small crack on the slope. The increasing of crack’s propagation impact the cohesion and internal friction angle which causing the soil on the slope shrinkage on its strength to shift and this could cause the avalanche on the slope. There are several inquiries had been conducted in the laboratory to further study the effect of the crack’s propagation towards cohesion and internal friction angle. The inquiry in the laboratory conducted using fricative test equipment with variation of crack’s propagation. The soil sample that were tested was from Lok Buntar village, Banjar district, South Kalimantan within the varied crack’s propagation. The cohesion value and internal friction angle from the inquiry were analyzed using Fellinius method using slope model from avalanche restoration project at Muara Teweh - Benangin road border, East Kalimantan. The result of the inquiry from the laboratory showed that the increasing of the crack’s propagation decreased the cohesion and internal friction angle, this put the safety factor of the slope in a critical condition with crack at 60%. This research is expected to be able to contribute on the prevention of the upcoming avalanche on a similar soil type and model